Pendugaan Umur Simpan Nupate (Nugget Patin Tempe) Menggunakan Metode ASLT (Accelerated Shelf Life Test) dengan Pendekatan Arrhenius - Atasasih, Hesti; Paramita, Irma Susan; Rahayu, Dewi (LPPM Hang Tuah Pekanbaru, 2024)
Patin fish nuggets are a processed form of fish that is finely ground, mixed with a binder and spices, then steamed and molded. 12 Nuggets are often added to other food ingredients to increase nutritional value, one of which is tempeh. It is hoped that the nutritional content of catfish and tempeh can meet nutritional intake needs, especially protein so that they can be an alternative to highly nutritious processed foods, however, there are problems in their use, namely that these two food ingredients are easily damaged, so that they remain available in the community they can be made into processed foods. One way to see the quality of food is to calculate its shelf life. This research aims to estimate the shelf life of Nupate (Patin Tempe Nuggets) using the ASLT method, with the Arrhenius approach, namely assessing the shelf life of food ingredients using water content as a critical point. The research was carried out at the integrated laboratory of the Riau Ministry of Health Polytechnic. The research results showed that the selected formula was P3, and then the water content was tested using thermography. The result of measuring the water content is 40.43%, which means it meets the requirements of SNI 7758:2013, namely less than 60%, then stored at a temperature of -5, a temperature of -10, and a temperature of -15, the higher the storage temperature, the higher the water content. contained therein, the lower the storage temperature, the lower the water content in it. The shelf life at -5 is 4 months, -10 is 6 months and -15 is 8 months. The research suggestion is to carry out microbiological, and chemical tests and packaging and labeling processes.